Football and football hooliganism - Williams, J.
On the development of football and football hooliganism in Great Britain. - Development of the football league attendance - Arrests at football matches - Problems in other coutries - Who are the hooligans and why do they do it? - Does drink have a part to play? - Are political groups involved? - Why football? - Is there hooliganism at other sports? - What is the role of the media? - How do the police cope? - What have the clubs and football authorities done? - What has the Football Trust done? - And the Government? - Charges for police attendance at Football League matches